Pollen Morphology of selected Heritiera Aiton. (Sterculioideae - Malvaceae s.l) species in Malaysia and its taxonomic significance - Ahmad Juhari, Amirul Aiman; Talip, Noraini; Che Amri, Che Nurul Aini; Ruzi, A.R.; Razali, Suhaniza; S, Idris; M.A., Nabila (2022)
Heritiera is a tropical and subtropical African, Asian and Pacific islands genus in the subfamily Sterculioideae (Malvaceae s.l). Its species are mainly trees of forests and mangroves at altitudes below 1000 m. This talk presents a palynological study of five species of Heritiera (H. littoralis Aiton, H. elata Ridl., H. simplicifolia (Mast.) Kosterm., H. sumatrana (Miq.) Kosterm., H. borneensis (Merr.) Kosterm.) by light microscopy (LM) and a scanning electron microscopy (SEM). Quantitative and qualitative data on pollen micromorphological characteristics were evaluated for taxonomic identification and species relationship using acetolysis single-grain technique. The effects of different types of coating and accelerating voltages during electron microscopy were also investigated. Pollen morphological features studied in this work included pollen ornamentation, echini arrangement, echini density, size, number and ornamentation of pores, polar and equatorial diameter, P/E ratio, exine thickness, colpus width and dimensions of lumen and murusPollen grains of all five species were colporate with tricolporate apertures and had rounded to lobate outlines. All species were monads and belonged to the same pollen class. Nevertheless, variations were observed in these features: ratio of exine thickness, pollen size, pore width and height, shape, colpus width and length, polar region index, exine ornamentation and size of lumen and murus. For example, Heritiera sumatrana can be differentiated from other species by its subprolate pollen shape, H. littoralis by its granulate ornamentation on the exine and small polar region index, and H. simplicifolia by its large polar region index. These diagnostic characteristics, specifically pollen surface, structure, size, shape, morphology, and texture, are valuable for the identification of taxa and can be used for delimitation of species. Hence, we developed a taxonomic key for a quick and accurate identification of Heritiera species. However, it was observed that different interpretations of pollen characteristics are possible based on the types of coating and accelerating voltage used. We found that gold coating was the best agent compared to others.